Desolvation of a novel microporous hydrogen-bonded framework: Characterization by in situ single-crystal and powder X-ray diffraction - Kepert, C; Hesek, D; Beer, P; Rosseinsky, M (1998)
Despite significant structural rearrangement upon desolvation of a three-dimensional molecular framework of hexaaquacobalt cations and redox- active functionalized tetrathiafulvalene anions (see the picture; the area filled with water molecules is shown in gray), monocrystallinity and microporosity are retained. X-ray analyses show that a unique combination of hydrogen bonds and π ·· π interactions within the framework gives this material a structural flexibility not seen in zeolites or their analogues.